The Use of Marine Invertebrates As An Early Indicator of Marine Pollution in The Coastal Zone of Negeri Latu, West Seram Regency - Fiyogi Derandy Alfarego Tuhumury; Nunun Ainun Putri Sari Banun Kaliky; Ahmad Ramdani Patty; Mujahiddin Permata Roman Rettob; Muhammad Fahrul Barcinta; Anggun Permata Sari (Pattimura University, 2025)
The coastal area of Negeri Latu, West Seram Regency, possesses a relatively high marine biodiversity and is a vital natural resource for the local economy, particularly in fisheries. However, increasing human activities around the coastal zone, such as the disposal of domestic waste, garbage, and industrial effluents, have exerted significant pressure on the quality of the marine environment. This study examines the utilization of aquatic biota as early pollution indicators in the coastal area of Negeri Latu, West Seram Regency. This research employs a descriptive quantitative approach. The coastline of Negeri Latu spans approximately 900 meters, with nine transects established perpendicular to the shoreline, each spaced 100 meters apart. Ten observation plots (1×1 m) were placed alternately along each transect at 10-meter intervals. Marine biota were observed, quantified, and identified to determine their species. The analysis results indicate that the pollution status in these waters falls under the Moderately Polluted category. This classification reflects a significant disturbance to water quality, although it has not yet reached severe pollution. The decline in water quality is attributed to various anthropogenic factors, particularly the local population’s high volume of waste disposal into the sea. The waste includes both organic and inorganic materials, contributing to marine environmental degradation through physical (e.g., water turbidity and discoloration), chemical (e.g., pH changes, increased levels of heavy metals and toxic compounds), and biological (e.g., reduced diversity and abundance of marine organisms) means.